A study investigating the treatment of equine squamous gastric disease with long‐acting injectable or oral omeprazole. Issue 2 (16th January 2020) - Gough, Sarah; Hallowell, Gayle; Rendle, David
Abstract: Background: Equine squamous gastric disease (ESGD) is a highly prevalent disease in horses, particularly in elite athletes. Some horses respond slowly, or fail to respond, to the licensed treatment, oral omeprazole (ORLO). Objectives: To compare rates of ESGD healing and improvement between ORLO and a long‐acting injectable omeprazole preparation (LAIO). Study design: Retrospective clinical study. Methods: The case records and gastroscopy images of horses presenting to Rainbow Equine Hospital over a 12‐month period were reviewed, with images being reviewed blind by one of the authors (David Rendle). Treatment responses were compared between horses that received 2 or 4 injections of 4 mg/kg LAIO at weekly intervals, and horses that received ORLO at 4 mg/kg PO SID for 4 weeks. Data were compared using a Mann–Whitney test with post hoc Dunn's test, chi‐squared test or Fisher's exact test. Results: Fifty‐six horses met the inclusion criteria: 29 received LAIO and 27 received ORLO. Treatment groups were comparable in terms of signalment and ESGD lesions. There was a difference in rate of healing when LAIO and ORLO treatment groups were compared at 28 days (LAIO‐97%; ORLO‐67%; p  = .005; OR = 14(1.8–158)), but no difference between LAIO at 14 days and ORLO at 28 days (LAIO‐86%; ORLO‐67%; p  = .12; OR = 3.1 (0.9–10)). Five localised and self‐limiting injection site reactions were identified in 3 horses out of 98 injections (5.1%). Main limitations: The study was limited by its retrospective nature, absence of randomisation and limited numbers. Conclusions: Four weeks of treatment with LAIO resulted in better rates of ESGD healing than 4 weeks of ORLO. Larger more robust studies of LAIO are warranted. Abstract : A retrospective clinical study comparing rates of ESGD healing and improvement between oral omeprazole and a long‐acting injectable omeprazole preparation in 56 horses. Ninety‐seven per cent of horses treated with long‐acting injectable omeprazole healed within 28 days compared with 67% of horses treated with oral omeprazole. In conclusion, 4 weeks of treatment with long‐acting injectable omeprazole resulted in better rates of ESGD healing than 4 weeks of oral omeprazole.